PENGARUH SEDEKAH BUMI TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN SAMBIKEREP KOTA SURABAYA PROVINSI JAWA TIMUR - Maya Putri Irawan, Laluna; Zola Mega Widya Kurnia Pratama Triadi, Febby (TANDA, 2022)
The Sedekah Bumi tradition is a customary ritual performed by communities across various regions in Indonesia, including Surabaya. It serves as an expression of gratitude to God for the blessings of agricultural harvests and as a prayer for a prosperous life. This tradition is passed down through generations and is routinely held at the end of each year. This study aims to examine and analyze the impact of the Sedekah Bumi tradition on the well-being of the people of Surabaya in social, economic, and cultural aspects using a literature review approach. The findings from the literature review indicate that Sedekah Bumi plays a significant role and has a positive influence on the community by strengthening social bonds, enhancing faith and awareness, supporting the local economy through collaboration, and preserving local cultural values. Overall, Sedekah Bumi is not merely a ritual but also a cultural activity that contributes to the welfare of the community.